Do We Need A Bone Block Procedure in Recurrent Anterior Shoulder Instability?: A Case Report - Hastomo Agung Wibowo; Dadang Rona Sasetyo; Yusa muhammad Thoriq; Felix Giovanni Hartono (Universitas Airlangga, 2023)
Background: Recurrent Anterior Shoulder Instability (RASI) is usually preceded by trauma. The incidence recurrence rate is high in trauma Induced RASI, especially in younger patients. The right diagnosis and management must be ruled out immediately for a better outcome. Case Report: The 28-year-old man complained of right shoulder instability for the past eight years, which worsened in the last year. The patient had a history of trauma. Anterior apprehension and relocation test for the right shoulder showed a positive result. Radiologic imaging showed bony bankart loss (27%) and an on-track hillsach lesion of the humeral head. The Instability Severity Index Score (ISIS) is 7 points. Based on these results, an open surgery bone block-Latarjet procedure was done. The surgery was successfully performed, and there was no sign of recurrent instability and pain after one year.Discussion: The number of recurrent shoulder dislocations is over 75%. Bone loss found in the patient will increase the chance of RASI. No block procedure effectively prevented future recurrence from the bone stop effect, which increases the glenoid cavity, stretching effect, and tensioning effect that prevents excessive humeral translation.Conclusion: In the case of RASI, treatment decisions need to be based on the patient's exact condition. Bone block-Latarjet procedure is indicated in patients with bony bankart loss >25%, on track hillsach lesion, and >6 ISIS. In this research, the patient showed improved functional and clinical outcomes after eight years of chronic shoulder instability.